Affinity through Vulnerability​: The Politics of Positionality in Child Welfare (Medicine Anthropology Theory, 2023)
Child welfare is a challenging space for professionals, parents, and most of all children. The labour of care within this space is an intersection of personal histories and ongoing narratives that synthesise self, family, medicine, and the state. I explore how encounters with children in care brought me into this nexus and redefined my position as a researcher. Competing perspectives on the role of experience in shaping affinity reveal a contentious discourse about what it means to be a foster child. In this Position Piece I find that sharing vulnerability through the traumatic experience of family estrangement is one path to mutual understanding that may transcend cultural boundaries. Further, mobilising and reflecting on the vulnerability of estrangement demonstrates the social embeddedness of mental health and healing.